Suillus sibiricus Singer, Farlowia 1945 - Palamarchuk, Marina A.; Kirillov, Dmitry V.; Shadrin, Dmitry M. (Zenodo, 2021)
Suillus sibiricus (Singer) Singer, Farlowia 2 (2): 260 (1945) (Fig. 3 e, f) Pileus 30–100 mm in diam., rounded convex, convex to expended, sometimes umbonate, viscid, light-yellow, brownyellow, with separate clear reddish-brown fibrous scales or spots, margin often appendiculate with soft white-yellow patches of veil tissue. Hymenophore as tubes, adnate or slightly decurrent, yellow, turning brown-yellow. Pores are angular, stretched in radial dimension, 1–2 mm in diam.. The young specimens with fibrous, white-yellowish partial veil, leaving more or less visible ring on the stipe. Stipe 50–110 × 5–15 mm, cylindrical, pale-yellow, covered by lightbrown, yellow-brown glandular dots, which turn brown-red when damaged or touched. Basidia 20–30 × 6–8 μm, narrow-clavate, 4-spores. Basidiospores (8.5)9–11(13) × 4–5 μm, Q = 2.1–2.5, fusiform, yellowish. Cystidia (cheilo-, pleuro- and caulocystidia) 35–73 × 6–9 μm, clavate or fusiform, hyaline or with brown or dark-brown content, fasciculate, surrounded with brown amorphous pigment at the base. Pileipellis consisting of intertwined gelatinous hyphae of 3–8 μm in diameter. Ecology and distribution . The species is widespread and form ectomycorrhizae with pines: in Europe (Alps, Tatras)—with Pinus cembra, P. peuce Griseb. (1846: 349) and P. strobus in China —with P. armandii Franch. (1884: 285) and P. koraiensis in North America—with P. monticola Douglas ex D. Don in Lambert (1832: 144) and P. flexilis (Munoz 2005; Wu et al. 2000). In Russia, Suillus sibiricus is wide spread in Siberia and Far East, rarely found in Northern Urals in forests with Pinus sibirica (Nezdojminogo 1969; Vassiljeva 1973; Petrov 1991; Perova & Gorbunova 2001; Perevedentseva 2008; Sazanova 2009; Gorbunova & Stepantsova 2015; Filippova & Bulyonkova 2017; Degteva 2019). Collection examined . RUSSIA, Troitsko-Pechorsky district, Pechoro-Ilychsky Nature Reserve, the settlement Yaksha, 61°49’18.6”N, 56°50’21.4”E, inside the settlement, near the tree of Pinus sibirica , 15 Jul. 2015, col. A. Bobretsov , SYKOf 2663; 6 km upstream the Pechora River from cordon Shezhym-Pechorsky, 62°03’39.2”N, 58°28’4.1”E, spruce green moss forest with Pinus sibirica and Abies sibirica , 31 Jul. 2015, col. A. Bobretsov , SYKOf 2668; place Log Iordanskogo, near the Medvezhya Cave, 62°00’42.8”N, 58°38’51.2”E, birch-spruce herb forest with Pinus sibirica , 18 Aug. 2003, col. M. Palamarchuk , SYKOf 2877. Vuktyl district, “Yugyd va” National Park, basin of the Schugor River, Nizhnie Vorota, right bank, lower course of the river Kyrtael, 64°13’12.1”N, 57°58’35.4”E, spruce herb forest with Pinus sibirica , 11 Aug. 2016, col. M. Palamarchuk , SYKOf 2521. Note . The most similar species ( S. acidus var. intermedius ), is distinguished by the absence of clear scales on the pileus, the presence of black glandular dots and a distinct ring on the stipe. : Published as part of Palamarchuk, Marina A., Kirillov, Dmitry V. & Shadrin, Dmitry M., 2021, Morphology and molecular data of the species of Suillus (Suillaceae, Boletales) associated with Pinus sibirica at the European northeast of Russia, pp. 18-34 in Phytotaxa 490 (1) on page 31, DOI: 10.11646/phytotaxa.490.1.2, http://zenodo.org/record/5756712 : {"references": ["Lambert, A. B. (1832) Description of the genus Pinus, with directions relative to the cultivation, and remarks on the uses of the several species: also, descriptions of many other new species of the family of Coniferae. Edition: [3 d ed. or editio minor]. London. 194 pp.", "Munoz, J. A. (2005) Boletus s. l. Fungi Europaei 2. Edizioni Candusso, Alassio. 820 pp.", "Wu, Q. X., Mueller, G. M., Lutzoni, F. M., Huang, Y. Q. & Guo, S. Y. (2000) Phylogenetic and biogeographic relationships of Eastern Asian and Eastern North American disjunct Suillus species (Fungi) as inferred from nuclear ribosomal RNA ITS sequences. Molecular Phylogenetics and Evolution 17 (1): 37 - 47. https: // doi. org / 10.1006 / mpev. 2000.0812", "Nezdojminogo, E. L. (1969) Ad floram Agaricalium litoris lacus Baical septentrionali-orientalis. Novosti sistematiki nizshikh rastenii 6: 146 - 158. [In Russian]", "Petrov, A. N. (1991) Synopsis of the flora of macromycetes of the Baikal region. Nauka, Novosibirsk. 81 pp. [In Russian]", "Perova, N. V. & Gorbunova, I. A. (2001) Macromycetes of south of the Western Siberia. Izdatelstvo SO RAN, Novosibirsk. 158 pp. [In Russian]", "Perevedentseva, L. G. (2008) Synopsis of agaricoid basidiomycetes of the Perm Krai. Perm State Pedagogical University, Perm. 86 pp. [In Russian]", "Sazanova, N. A. (2009) Macromycetes of the Magadan Region. SVNC DVO RAN, Magadan. 196 pp. [In Russian]", "Filippova, N. V. & Bulyonkova, T. M. (2017) The diversity of larger fungi in the vicinities of Khanty-Mansiysk (middle taiga of West Siberia). Environmental Dynamics and Global Climate Change 8 (1): 13 - 24. https: // doi. org / 10.17816 / edgcc 8113 - 24", "Degteva, S. V. (2019) The Red Data Book of the Komi Republic. Komi Republican Printing House, Syktyvkar. 768 pp."]}